STRATEGI PEMBERIAN INFORMASI AKUNTANSI UNTUK MENGURANGI ESKALASI KOMITMEN - RIZKIANO TANJUNG (Universitas Katolik Widya Mandala Surabaya, 2012)
In thebusiness world, decision making is very influential on the future of the business. A manager of the company is required to be able to make decisions that provide benefit forthe company. But in reality, managers sometimes do their regularities in the decision making process. One of these irregularities is the escalation of commitment. Lack ofinformation held bymanagersduringdecision making processcan trigger the occurrenceescalation ofcommitment. Information that can be used by managers one of which is the accounting information. It is expected a manager can use the accounting information as a strategy in decision making process so it can reduce the occurrence of escalation of commitment. With theexistence of a dequate and accurate information, managers are expected toimplement the decision making process with the appropriate and in accordance with theproblems facedby the business project. If the manager has taken a decision in accordance with the objectives of the company, the managers have been avoided from acts of escalation of commitment.